Sex ratios and the city: Secondary offspring sex ratios, parental corticosterone, and parental body condition in an urban-adapted bird - Kilgour, Denyelle A. V.; Linkous, Courtney R.; Pierson, Todd W.; Guindre-Parker, Sarah (Frontiers in Ecology and Evolution, 2022)
The Trivers-Willard hypothesis states that mothers should adjust their offspring sex ratio according to their own condition and the environment they face during breeding. Past tests of this hypothesis have focused on how natural variation in weather, food availability, or predation pressure shapes sex allocation trade-offs. However, anthropogenic activities, such as urbanization, can alter all of the above characteristics presenting animals with novel challenges in optimizing their brood sex ratio. Previous research has examined how urban living influences individual body condition in several bird taxa, but few have explored subsequent impacts on secondary offspring sex ratio. One likely mediator of the link between environmental conditions, parental condition, and sex ratios is corticosterone (CORT), the primary glucocorticoid in birds. Research on CORT’s influence on sex ratios has focused solely on maternal CORT. However, for species with biparental care, paternal CORT or the similarity of maternal and paternal phenotypes may also help ensure that offspring demand matches parental care quality. To test these hypotheses, we explore offspring secondary sex ratios in European starlings (Sturnus vulgaris). We did not find an effect of site or parental body condition on the production of the more costly sex (males). Instead, we found preliminary evidence suggesting that the similarity of maternal and paternal CORT levels within a breeding pair may increase the likelihood of successfully fledging sons. Maternal and paternal CORT were not significant predictors of secondary sex ratio, suggesting that parental similarity, rather than parental CORT alone, could play a role in shaping secondary offspring sex ratios, but additional work is needed to support this pattern. Starlings are considered an urban-adapted species, making them a compelling model for future studies of the relationship between urbanization, parental body condition, and sex ratios.